Hematological Markers as Predictors of Severity and Outcomes in Firearm Injuries - Malik, Ahmed Hassaan; Amir, Mumtaz; Saleem, Muhammad Rehan; Ahmed, Zulfiqar; Hamid, Arslan (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the hematological parameters of firearm injury patients on presentation with severity of sustained injuries and to determine the relationship of these hematological parameters with hospital stay duration. Study Design: Prospective Comparative Study. Place and Duration of Study: Surgery Department of Secondary Care Hospital Bannu, Pakistan, from Jul 23 to Jun 24. Methodology: Two hundred and fifty patients presenting to emergency department with firearm injuries were included. All patients underwent complete blood picture analysis on presentation. Patients were followed throughout admission, and blood parameters on arrival were compared with injury severity scores (ISS) and duration of hospital admission. Results: The median (IQR) age of the study population was 30(25-36) years and 152(60.8%) had sustained severe injuries as per ISS. Median (IQR) hospital admission was 5(2-8) days. Statistically significant association was found between ISS and total leukocyte count, red blood cell count, hemoglobin level, hematocrit, neutrophil count, and lymphocyte count on presentation (p-values <0.05). There was also a statistically significant association between hospital admission duration and total leukocyte count, red blood cell counts, hemoglobin level, hematocrit, neutrophil count, lymphocyte count, and red cell distribution width on presentation (p-values <0.05). Conclusion: Several hematological parameters of firearm injury patients on presentation are associated with severity of sustained injuries and duration of hospital stay. Neutrophil counts, lymphocyte counts, and red cell distribution width on presentation may serve as important markers for determining severity of injuries and hospital stay in firearm injury patients.